Increased expression of NLRP3 inflammasome in placentas from pregnant women with severe preeclampsia - Weel, Ingrid C. [UNESP]; Romao-Veiga, Mariana [UNESP]; Matias, Mariana L. [UNESP]; Fioratti, Eduardo G. [UNESP]; Peracoli, Jose C. [UNESP]; Borges, Vera T. [UNESP]; Araujo, Joan P. [UNESP]; Peracoli, Maria T. [UNESP] (Elsevier B.V., 2017)
Preeclampsia is a pregnancy disorder characterized by imbalance between pro- and anti-inflammatory cytokines associated with high plasma levels of uric acid and Interleukin-1 beta (IL-1 beta). The inflammasome is a protein complex that mediates innate immune responses via caspase-1 activation promoting secretion of IL-1 beta and IL-18 in their active forms, and also release of the high-mobility group box 1 protein (HMGB1). As the placenta seems to play an important role in the pathogenesis of PE, the present study investigated the expression of genes and proteins related to the inflammasome in placentas from pregnant women with severe preeclampsia. Placental tissue was collected from 20 normotensive pregnant women and 20 preeclamptic women, and inflammasome components, NLRP3 (NOD-like receptor family, pyrin domain-containing protein 3), caspase-1, IL-1 beta and IL-18, as well as tumor necrosis factor-alpha (TNF-alpha) and HMGB1 were evaluated by immunohistochemistry, enzyme linked immunosorbent assay (ELISA) and also quantified by reverse transcription-qPCR (RT-qPCR). Compared with normotensive pregnant women, placenta from women with PE showed a significant increase in NLRP3, caspase-1, IL-1 beta, TNF-alpha and HMGB1 mRNA. Immunohistochemical staining of NLRP3, caspase-1, IL-1 beta and TNF-alpha in placental villi, as well as the levels of caspase-1, TNF-alpha and HMGB1 in placental homogenate were significantly higher in the preeclamptic group than in the normotensive group. However, mRNA expression of IL-18 and its protein concentrations were lower in placentas from preeclamptic women. The results suggest that placentas from pregnant women with preeclampsia show higher expression of NLRP3 inflammasome, which may be involved in the exaggerated inflammatory state in preeclampsia.
Keywords: Cytokines; Immunohistochemistry; Inflammasome; Placenta; RT-qPCR